The relationship between anthropometry and hand grip strength among older Malaysian people - N. S. M., Shalahim (2016)
Physiological changes and loss of hand grip strength are natural consequences of the ageing process. Previous studies have shown that physiological changes will affect the hand grip strength of elderly people. However, to date, there are no studies which have developed models that predicts the hand grip strength of elderly Malaysians as a function of anthropometric dimensions. Knowledge on the correlation between these variables is crucial in order to create a suitable living environment as well as designing and developing products that cater specifically to the needs of the elderly. Hence, the main objective of this study is to examine the correlation between anthropometric dimensions and hand grip strength in a representative sample of the elderly population in Malaysia and developing the regression models that predicts the hand grip strength of elderly Malaysian males and females.